If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -22 + -1w = 8(6 + -8w) + -7 -22 + -1w = (6 * 8 + -8w * 8) + -7 -22 + -1w = (48 + -64w) + -7 Reorder the terms: -22 + -1w = 48 + -7 + -64w Combine like terms: 48 + -7 = 41 -22 + -1w = 41 + -64w Solving -22 + -1w = 41 + -64w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '64w' to each side of the equation. -22 + -1w + 64w = 41 + -64w + 64w Combine like terms: -1w + 64w = 63w -22 + 63w = 41 + -64w + 64w Combine like terms: -64w + 64w = 0 -22 + 63w = 41 + 0 -22 + 63w = 41 Add '22' to each side of the equation. -22 + 22 + 63w = 41 + 22 Combine like terms: -22 + 22 = 0 0 + 63w = 41 + 22 63w = 41 + 22 Combine like terms: 41 + 22 = 63 63w = 63 Divide each side by '63'. w = 1 Simplifying w = 1
| y=6x^2-8 | | 14=5-3x | | -3+2m=-15 | | 81607=n+73142 | | 2k+4=5k-4 | | 81,607=n+73,142 | | 28-d=14 | | -(7x-4)+5x-8=-4 | | .8x-.1=.3 | | 145=-98 | | 16t^2-27t+10=0 | | 8y+3=35 | | 11x+11=9x+23 | | 8-12s=32 | | 3s-1=4s+5 | | 11x+11 = +9x+23 | | [2](4x-2)=log[2](2x+5) | | 3x+4y-7=-2x+2y-5 | | [2](4x-2)=7log[2](2x+5) | | X+3t=13 | | X-6y=17X-fory | | 20=(-8)+t | | [2](4x-2)=7-log[2](2x+5) | | 4n+8-9n=-5+5n+13 | | 3w=6+-9 | | log[2](4x-2)=7-log[2](2x+5) | | 32-2(y-5)-2z=3(z+7)-10 | | 3(4)-3=9 | | m+7m-8=-2m | | 6v-5=41 | | 4X^3-24X^2+34X-8=0 | | 250+350=m-18+m |